Recent developments in the determination of the amplitude and phase of quantum oscillations for the linear chain of coupled orbits: Магнитоквантовые осцилляции - Audouard, Alain; Fortin, Jean-Yves (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
De Haas-van Alphen oscillations are studied for Fermi surfaces (FS) illustrating the model proposed byPippard in the early sixties, namely the linear chain of orbits coupled by magnetic breakdown. This FS topologyis relevant to many multiband quasi-two-dimensional (q-2D) organic metals such as -(BEDT–TTF)2Cu(NCS)2 and -(BEDT–TTF)4CoBr4 (C6H4Cl2) which are considered in detail. Whereas the Lifshits–Kosevich model onlyinvolves a first order development of field- and temperature-dependent damping factors, second order termsmay have significant contribution to the Fourier components amplitude for such q-2D systems at high magneticfield and low temperature. The strength of these second order terms depends on the relative value of the involveddamping factors, which are in turns strongly dependent on parameters such as the magnetic breakdown field, effective masses and, most of all, effective Landé factors. In addition, the influence of field-dependent Onsagerphase factors on the oscillation spectra is considered.